The STUDENT SATISFACTION OF ITSK Acupuncture Study Program RS dr. SOEPRAOEN KESDAM V/BRW MALANG TOWARDS ONLINE LEARNING METHODS - Mayang Wulandari; Chantika Mahadini (Institut Teknologi, Sains, dan Kesehatan RS dr. Soepraoen Malang, 2022)
Introduction. The online learning method has never been imagined and planned before, but because of an emergency situation for the sake of safety, anything is done so that education continues with all its advantages and disadvantages. Improvements and independent innovations continue to be carried out, the readiness of devices, network quality, internet quota, and the readiness of human resources are the main needs at this time. Methode The method used is a qualitative descriptive analysis approach to process the primary data obtained. The population in this study were students of the ITSK Acupuncture Study Program, Dr. Soepraoen Kesdam V/BRW Malang, with a total sampling of 231 people. The research data was obtained using a questionnaire / google form which was filled out online by students. Analysis of student responses using the Guttman Scale. Results From a total of 231 students answered 9 questions about E learning with the result that 227 knew, 230 could operate, 220 answered lectures were still interesting, 223 answered with E learning that lectures became flexible, 202 answered that learning outcomes could be optimal, 222 people answered with E learning that they could still communicate with lecturers, 216 were satisfied, 222 answered with E learning that lectures were more cost-effective, and 200 felt that it was better to use E learning for the next lecture. Conclusion. Students of ITSK Acupuncture Study Program dr. Soepraoen Kesdam V/BRW Malang are satisfied with the Online Learning Method. Keywords: Flexible, Online, Satisfaction.